Tibial plateau leveling osteotomy and tibial tuberosity advancement – a systematic review - Beer, Patricia; Bockstahler, Barbara; Schnabl-Feichter, Eva (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2018)
Objective: The optimal surgical technique for treatment of cranial cruciate ligament rupture in canine has been scientifically discussed for decades. Despite the continuous debate, proximal tibial osteotomies such as tibial plateau leveling osteotomy (TPLO) and tibial tuberosity advancement (TTA) are increasingly common. The objective of this review was to systematically evaluate the literature reporting outcome and complications associated with TPLO and TTA. Materials and methods: A systematic search of literature databases identified articles published from August 2004 to February 2016 describing evaluations of short- or longterm outcomes as well as complications following TPLO or TTA. Results: Ninety-one studies were included in this review and assigned to one out of four evidence levels. Of those, 89 studies provided the lowest evidence level and only two were assigned to the third-best evidence level. A comparison of subjective gait analyses could not detect differences in the decrease of lameness between TPLO and TTA, while objective gait analysis supports the superiority of TPLO. Fewer patients treated with TPLO were diagnosed with postoperative joint instability and TPLO had a lower percent increase of osteoarthritis (OA) after surgery. Owner satisfaction was high for both techniques. For TPLO and TTA the average total, minor, major and catastrophic complication rates were 15.9 % and 20.8 %, 7.9 % and 11.6 %, 5.2 % and 13.2 % as well as 0.8 % and 5.6 %, respectively. Conclusion and clinical significance: The assessed literature supports the hypothesis that TPLO is associated with lower complication rates, an improved clinical-functional outcome and less increase of OA compared to TTA. The results are indicative for a long-term restoration of normal limb function after TPLO. However, the strength of available evidence and the comparability of each study’s results were poor and more comparative studies are needed to draw strong conclusions towards the superiority of the TPLO over the TTA.Gegenstand und Ziel: Die optimale chirurgische Technik zur Behandlung der Ruptur des vorderen Kreuzbands beim Hund ist seit Jahrzehnten ein viel diskutiertes Thema in der Kleintierorthopädie. Trotz anhaltender Diskussionen werden Osteotomietechniken der Tibia, die Tibial Plateau Leveling Osteotomy (TPLO) und das Tibial Tuberosity Advance ment (TTA), immer häufiger angewendet. In diesem Artikel werden die in der Literatur beschriebenen Ergebnisse und Komplikationen nach einer TPLO und TTA systematisch zusammengefasst und verglichen. Material und Methoden: Nach systematischer Literaturrecherche zu klinischen Studien über TPLO oder TTA wurden zwischen August 2004 und Februar 2016 publizierte Studien inkludiert, die über Kurz- oder Langzeitergebnisse und Komplikationen berichteten. Ergebnisse: Die 91 analysierten Studien wurden einer von vier Evidenzklassen zugeteilt. Zwei Studien entsprachen der drittbesten Evidenzklasse, 89 der niedrigsten Evidenzklasse. Ein Vergleich der Ergebnisse subjektiver Lahmheitsuntersuchungen zeigte keine eindeutigen Unterschiede zwischen den Techniken. Objektive Ganganalysen wiesen auf bessere Resultate nach TPLO hin. Die TPLO war mit einer geringeren postoperativen Zunahme der Osteoarthritis (OA) verbunden und bei weniger Patienten wurde postoperativ eine Gelenkinstabilität diagnostiziert. Die durchschnittlichen Gesamtkomplikationsraten betrugen für die TPLO und TTA 15,9 % bzw. 20,8 %, die gering-, mittel- und hochgradigen Komplikationsraten 7,9 % bzw. 11,6 %, 5,2 % bzw. 13,2 % sowie 0,8 % bzw. 5,6 %. Schlussfolgerung und klinische Rele vanz: Aktuelle Publikationen stützen die Hypothese, dass die TPLO mit besseren klinisch-funktionellen und radiologischen Ergebnissen, einer geringeren Zunahme der OA sowie geringeren Komplikationsraten einhergeht. Die Resultate der Studie lassen auf eine Lang-zeitwiederherstellung der normalen Giedmaßenfunktion nach einer TPLO schließen. Zu beachten sind jedoch das niedrige Evidenzniveau und die limitierte Vergleichbarkeit der Resultate verschiedener Studien. Um eindeutige Aussagen bezüglich der Überlegenheit der TPLO gegenüber der TTA ziehen zu können, bedarf es weiterer Vergleichsstudien.
Keywords: Stifle joint; complications; TPLO; TTA; cranial cruciate ligament